Private information and lender discretion across time and institutions - Gene Ambrocio; Iftekhar Hasan (Bank of Finland, 2018)
We assess the extent to which discretion, unexplained variations in the terms of a loan contract, has varied across time and lending institutions and show that part of this discretion is due to private information that lenders have on their borrowers. We find that discretion is lower for secured loans and loans granted by a larger group of lenders, and is larger when the lenders are larger and more profitable. Over time, discretion is also lower around recessions although the private information content is higher. The results suggest that bank discretionary and private information acquisition behaviour may be important features of the credit cycle.
URN:NBN:fi:bof-201810112084
Keywords: D82; G14; G21; G28; 330